Learned in the Trenches Insights into Leadership and Resilience Compiled by Two Women Leaders in Energy - Capello, Maria Angela (Cham : Springer International Publishing, 2018)
This book shares the learnings and perspectives of two pioneer women who waded the many challenges posed by multiculturalism and gender in one of the corporate environments more rigid and traditional in the business world: the energy sector in the Middle East. How they managed to create a growth space for themselves and their teams is a story of professional and personal tenacity, shaping a privileged perspective that enabled them to understand the root causes of barriers, as well as envision plausible solutions. They propose in the book not only their vision, but a remarkable collection of unfiltered interviews to influential leaders in the energy sector, to complete a vision of what is key to achieve success when leading or consulting in a corporate environment. The book offers a compilation of very personal approaches to professionalism, resilience, work, and ultimately, success, from within and outside the ranks of highly regarded corporations in the energy sector. The ultimate aim is that of triggering a self-reflection in the readers, grounded on the learnings and perspectives of those who made it to the highest roles of one of the less understood business environments.
Introduction -- The corporate Environment -- Inside and Out.- The Real-Cases.- Invited interviews -- Learnings -- Conclusions.
Business and Management
text file PDF
Keywords: Business; Economic geology; Leadership; Energy systems; Supervision; Counseling; Energy policy; Energy and state